Factors Affecting the Adoption Intention Mobile Payment of OVO in Surabaya - Arifin, M Jainal; Rahardja, Christina; Anandya, Dudi (International Journal Labs, 2022)
Background: Provide an adequate background covering the literature review and the gap of the research with other relevant former research works. Aim: This study aims to determine the Factors Affecting Adoption Intention to OVO Mobile Payment Users in Surabaya. Method: This type of research is basic business research using a quantitative approach with data analysis in the form of SEM (Structural Equation Model). Management of data in this study using AMOS 22.0 for windows which are used in testing the Measurement Model (Outer Model) and Structural Model (Inner Model). The sampling technique used is 300 respondents with the last education of SMK/SMA and have used m-payment OVO in the last 6 months and who are domiciled in Surabaya. Findings: The results showed that Perceived Transaction Convenience (PCT), Compatibility (COM), Relative Advantage (RA), Government Support (GS), Additional Value (AV), Perceived Risk (PSR), Absorptive Capacity (AC), Affinity (AFFI), and Personal Innovativeness in Information Technology (PIIT) is proven to have a significant effect on Adaptation Intention (AI). In addition, Social Influence (SI) has been shown to have non-significant results on the Adaptation Intention (AI) of OVO mobile payment users in Surabaya.